The Relationship between Students’ Cultural Habits, Hearsay Exposure, and the Importance of English - Laoli, Adieli; Waruwu, Puspa Triyani; Cui, Siti Khafifah Shaleh N.; Halawa, Arif Wahyu Tomosa; Laia, Agustina (Universitas Pahlawan Tuanku Tambusai, 2026)
English plays a crucial role as a global language; however, students’ perceptions of its importance are shaped by their sociocultural environment. In addition to cultural habits reflected in daily community practices, students are also influenced by hearsay exposure, defined as repeated informal messages or opinions about English transmitted through family, peers, and community discourse. Previous studies have largely examined cultural or social belief factors separately, leaving limited understanding of their combined influence. This study aimed to investigate the relationship between students’ cultural habits, hearsay exposure, and their perceived importance of English at SMA Negeri 1 Lahewa. Using a quantitative correlational design, data were collected from 96 eleventh-grade students through a Likert-scale questionnaire and analyzed using Pearson correlation and multiple regression. The findings revealed that both cultural habits and hearsay exposure significantly correlated with students’ perceived importance of English, both individually and simultaneously. These variables collectively explained a substantial proportion of variance in students’ perceptions. The study highlights that students’ evaluations of English are socially constructed and underscores the need for culturally responsive English teaching that addresses prevailing community narratives.